FORMULASI DAN UJI SIFAT FISIK SEDIAAN KRIM EKSTRAK KULIT JERUK KEPROK (Citrus reticulata) MENGGUNAKAN BASIS CERA ALBA - Erma Yunita (Jurnal Penelitian Farmasi Indonesia)
One of the citrus crops in Indonesia is tangerine (Citrus reticulata). The part that is used as vitamins are citrus fruits. The skin is not used by the community, because it is often found as environmental waste. Orange peel can actually be used as a source of medicinal materials, because it can be used as an antioxidant. This study will make the cream using a base cera alba intended to get cream with good physical preparations. This research is a type of experimental research. Extraction method used is maseration method with 70% ethanol solvent. Making creams made in 3 formulas are F1, F2 and F3. The bases used are cera alba with concentration of 3 formula consecutively as much as 2.5g, 5g, and 10g. The physical properties of the cream conducted to determine the physical properties of good cream include organoleptic test, pH test, homogeneity test, and sticky power test. The results of the test of physical properties of cream tangerine peel extract made in cream dosage from using cera alba base this is stable and has physical characteristic test according to requirement on organoleptic test, pH test, and sticky test. Then on the physical test of spreading power and homogeneity, cream of tangerine peel extract (Citrus reticulate) with cera alba base 2.5 – 10g did not has the requirement of goog cream. Keyword: Formulation, cream preparation, tangerine peel (Citrus reticulata), alba case base, physical properties test.